Exploring the role of serum sestrin 2 in patients with endometrial polyps and uterine leiomyomas: implications for early diagnosis and pathophysiology - Akkaya, Selim; Bornaun, Teymur; Güven, Hamit Zafer (The European Research Journal, 2024)
Endometrial polyps and uterine leiomyomas are common gynecological conditions that significantly affect women’s health. Recent studies have begun to explore potential biomarkers that could assist in the early diagnosis and understanding of the pathophysiology of these conditions. One such biomarker is Serum Sestrin 2 (SESN2), a protein involved in cellular stress response. This review aims to synthesize research findings on the relationship between serum SESN2 levels and the presence of endometrial polyps and uterine leiomyomas. It examines the potential of SESN2 as a diagnostic tool and its role in the underlying mechanisms of these conditions. Studies suggest that SESN2 levels are elevated in patients with these conditions compared to controls, indicating its involvement in their pathophysiology. Furthermore, the review discusses the implications of these findings for clinical practice, particularly in terms of early detection and targeted therapies. Future research directions and the need for large-scale studies to validate SESN2 as a clinical marker are also addressed. This review highlights the importance of biomarkers like SESN2 in enhancing our understanding and management of gynecological disorders.